2017
DOI: 10.4236/ce.2017.89099
|View full text |Cite
|
Sign up to set email alerts
|

Animated Videos Prove to be Beneficial in Teaching English Grammar as EFL: A Neurological Study of How Students Learn and Retain English Grammar

Abstract: In the education field, there are different theories that apply to teaching in general and specific ones targeting mode of teaching English grammar as a foreign language. This study involves neurological evidence through using animation videos which promotes the idea that learning and teaching in an enjoyable environment are much more conducive, than learning in an unpleasant environment. Using animated videos presentations in teaching students English grammar by explaining the English grammar rules, the used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…• The students were shown documentaries and video clips in the past, in the War Ethics course, but they liked better watching an entire movie [11].…”
Section: B Results Of the Interviewmentioning
confidence: 99%
See 1 more Smart Citation
“…• The students were shown documentaries and video clips in the past, in the War Ethics course, but they liked better watching an entire movie [11].…”
Section: B Results Of the Interviewmentioning
confidence: 99%
“…Films have been used extensively in language courses [11], but rarely in engineering and science. [7].…”
Section: Movies In Educationmentioning
confidence: 99%
“…Researcher also concluded that the results of research were similar to previous research that researcher used as base of this research. As Mushtaq and Zehra (2016:77-86), Abdo and Al-Awabdeh (2017:1416-1422, Isna (2018:51-56), Saindra and Mutiarani (2018:60-62), and Mahmudah and Izzah (2019:89-93)proved that visual material was effective on teaching English lesson including English Tenses.…”
Section: Experiments Al Classmentioning
confidence: 94%
“…Later, Abdo and Al-Awabdeh (2017:1416-1422 explains as they compared the results between English-dubbed animation and traditional technique, there was improvement in student comprehension for Past Tenses because they found out that there was decrease of student grammatical errors in post-test compared pretest. They also added that visual material enhanced student thought and students were motivated and could comprehend the Tense easily during the lesson.…”
Section: Introductionmentioning
confidence: 99%
“…Globalization and technological advancements have led to a rise in the usage of English by non-native speakers (Lee & Lee, 2019; Abdo et al, 2017). In addition, English is widely spoken worldwide and many people study it as a second language (L2) or as a foreign language (FL).…”
Section: Introductionmentioning
confidence: 99%